2015
DOI: 10.1002/adfm.201500865
|View full text |Cite
|
Sign up to set email alerts
|

Realization of Boolean Logic Functionality Using Redox‐Based Memristive Devices

Abstract: Emerging resistively switching devices are thought to enable ultradense passive nanocrossbar arrays for use as random access memories (ReRAM) by the end of the decade, both for embedded and mass storage applications. Moreover, ReRAMs offer inherent logic‐in‐memory (LIM) capabilities due to the nonvolatility of the devices and therefore great potential to reduce the communication between memory and calculation unit by alleviating the so‐called von Neumann bottleneck. A single bipolar resistive switching device … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
91
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 137 publications
(93 citation statements)
references
References 51 publications
0
91
0
Order By: Relevance
“…Hence, we explain briefl y the CRS-logic concept introduced by Linn et al, [ 5 ] which has been recently demonstrated for different devices. [ 30 ] By using this logic concept, a single bipolar switching device is capable to perform 14 out of 16 Boolean functions. The remaining two operations XOR and XNOR can be realized by two devices.…”
Section: Basics Of the Crs-logicmentioning
confidence: 99%
“…Hence, we explain briefl y the CRS-logic concept introduced by Linn et al, [ 5 ] which has been recently demonstrated for different devices. [ 30 ] By using this logic concept, a single bipolar switching device is capable to perform 14 out of 16 Boolean functions. The remaining two operations XOR and XNOR can be realized by two devices.…”
Section: Basics Of the Crs-logicmentioning
confidence: 99%
“…It might even be increased by stacking multiple layers of passive matrices to a 3D structure. [7][8][9][10][11][12][13][14][15][16][17][18] Threshold devices show an abrupt resistance change at a certain voltage stress V Th,ON . [ 1,4 ] This serious issue is alleviated by either complementary resistive switching devices or by the integration of a selector device in addition to the passive ReRAM, so called "1S1R" structures.…”
Section: Introductionmentioning
confidence: 99%
“…These two stable states of the device are sufficient for its application as a non-volatile memory, also denominated resistive random access memory (RRAM), and logic devices [5,6].…”
Section: Introductionmentioning
confidence: 99%